2022
DOI: 10.7717/peerj.14298
|View full text |Cite
|
Sign up to set email alerts
|

A new species and new records species of Pluteus from Xinjiang Uygur Autonomous Region, China

Abstract: Xinjiang Uyghur Autonomous Region in China embraces a unique geographical and ecological environment, and the macrofungi represent a rich resource. However, few studies on the genus Pluteus have been reported from Xinjiang. In 2021, the macrofungal resources in Xinjiang were surveyed, and 10 specimens belonging to the genus Pluteus were collected. Based on the morphological study and molecular analysis, three species were recognized, P. aletaiensis, P. brunneidiscus, and P. hongoi. Pluteus aletaiensis is propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
(53 reference statements)
0
0
0
Order By: Relevance
“…The range of b–c contains a minimum of 90% of the measured values. Extreme values (i.e., a and b) are given in parentheses ( Qi et al 2022 ).…”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The range of b–c contains a minimum of 90% of the measured values. Extreme values (i.e., a and b) are given in parentheses ( Qi et al 2022 ).…”
Section: Materials and Methodsmentioning
confidence: 99%
“…The species that were morphologically similar to new species, newly recorded species, and common species, and have high sequence similarity after blast were selected ( Justo et al 2011b , 2012 ; Menolli et al 2015 ; Desjardin and Perry 2018 ; Hosen et al 2019 ; Hosen et al 2021 ; Ševčíková et al 2022; Qi et al 2022 ; Malysheva et al 2023 ; Ševcíková et al 2023 ; Xu et al 2023 ), and details of the ITS and TEF1-α sequences of these species are shown in Table 1 . The ITS and TEF1-α dataset comprised 134 representative sequences that exhibited the highest similarity to Pluteus spp., and two sequences of Volvopluteus michiganensis (A.H.…”
Section: Materials and Methodsmentioning
confidence: 99%